2019
DOI: 10.1101/643189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retinal stabilization reveals limited influence of extraretinal signals on heading tuning in the medial superior temporal area

Abstract: Heading perception in primates depends heavily on visual optic-flow cues. Yet during self-motion, heading percepts remain stable even though smooth-pursuit eye movements often distort optic flow. Electrophysiological studies have identified visual areas in monkey cortex, including the dorsal medial superior temporal area (MSTd), that signal the true heading direction during pursuit. According to theoretical work, self-motion can be represented accurately by compensating for these distortions in two ways: via r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…5,7). A similarly broad range of rotation tolerance has been observed in previous studies of rotation compensation in MSTd (Yang and Gu, 2017;Manning and Britten, 2019) and VIP (Sunkara et al, 2015). Since the problem that eye rotation poses on the visual system is at least partially solved at the level of human behavior (Warren and Hannon, 1988;Royden et al, 1992), rotation compensation may be solved progressively in the brain at the systems level or, perhaps, complete rotation compensation in visual neurons is not necessary to guide behavior (Cutting et al, 1992).…”
Section: Discussionsupporting
confidence: 59%
“…5,7). A similarly broad range of rotation tolerance has been observed in previous studies of rotation compensation in MSTd (Yang and Gu, 2017;Manning and Britten, 2019) and VIP (Sunkara et al, 2015). Since the problem that eye rotation poses on the visual system is at least partially solved at the level of human behavior (Warren and Hannon, 1988;Royden et al, 1992), rotation compensation may be solved progressively in the brain at the systems level or, perhaps, complete rotation compensation in visual neurons is not necessary to guide behavior (Cutting et al, 1992).…”
Section: Discussionsupporting
confidence: 59%
“…However, these previous studies used stimuli containing insufficient visual cues (e.g., lack of depth cue), and this potentially undermined the retinal contributions. In particular, recent neurophysiologic studies using novel optic‐flow stimuli (with enriched visual cues, e.g., depth and perspective cues) have shown that the retinal mechanism played a dominate role in distortion compensation at the single‐neuron level (Bremmer, Kubischik, Pekel, Hoffmann, & Lappe, ; Kaminiarz, Schlack, Hoffmann, Lappe, & Bremmer, ; Manning & Britten, ; Sunkara, DeAngelis, & Angelaki, ). Our result of training‐induced improvement in self‐motion perception without actual eye movement appears to add a new twist to this retinal versus extraretinal debate.…”
Section: Discussionmentioning
confidence: 99%
“…Video 3 and 12). Interestingly, although neurons in both MST and VIP signal heading, they do not strongly discriminate between the retinal patterns generated by simulated, as opposed to real, eye movements (Sunkara et al, 2015;Manning & Britten, 2019).…”
Section: Cortical Involvement In the Perception Of Optic Flowmentioning
confidence: 94%